2020
DOI: 10.1051/medsci/2020173
|View full text |Cite
|
Sign up to set email alerts
|

Les myélinosomes : une nouvelle voie du contrôle de qualité des protéines

Abstract: Deux voies de dégradation des protéines mal repliées sont classiquement décrites : la voie du protéasome et la voie de l’autophagie. Nous décrivons ici une nouvelle voie de protéostase cellulaire ne dégradant pas la protéine anormale mais l’expulsant hors de la cellule grâce à des nanovésicules appelées myélinosomes. Ces myélinosomes sont produits par la cellule dans des situations pathologiques ou de stress en lien avec des facteurs génétiques ou environnementaux. Sur le plan morphologique, les myélinosomes s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…It has been suggested that Sertoli cells remove the misfolded proteins through this myelinosome-mediated secretion, thus preserving cellular proteostasis. While rare in normal cells, intracellular myelinosomes appear in pathological situations caused by genetic or environmental factors [ 15 ]. They are also detected and abundant in aggregation diseases such as Huntington’s disease or cystic fibrosis [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that Sertoli cells remove the misfolded proteins through this myelinosome-mediated secretion, thus preserving cellular proteostasis. While rare in normal cells, intracellular myelinosomes appear in pathological situations caused by genetic or environmental factors [ 15 ]. They are also detected and abundant in aggregation diseases such as Huntington’s disease or cystic fibrosis [ 16 ].…”
Section: Introductionmentioning
confidence: 99%